Flow Cytometry Detection of Platelet Procoagulant Activity and Microparticles in Patients with Unstable Angina Treated by Percutaneous Coronary Angioplasty and Stent Implantation - Vidal, Catherine; Spaulding, Christian; Picard, Françoise; Schaison, Frédéric; Melle, Josiane; Weber, Simon; Fontenay-Roupie, Michaëla (Thrombosis and Haemostasis, 2001)
Platelet activation is known to participate to the pathogenesis of acute coronary syndromes. Aminophospholipid exposure and micro-particles shedding are hallmarks of full platelet activation and may account for the dissemination of prothrombotic seats. Using flow cytometry analysis of annexin V binding to externalized aminophospholipids, we followed platelet procoagulant activity (PPA) and platelet microparticles (PMP) shedding in venous and coronary whole blood samples from 30 patients with unstable angina before and after percutaneous coronary angioplasty (PTCA) and stent implantation. Baseline values of PPA and PMP were significantly more elevated in patients than in control subjects (p <0.005). PMP percentage was significantly higher in coronary than in venous blood, and in coronary blood of patients with proximal instead of mid/distal lesions of coronary arteries. No enhancement of platelet reactivity to TRAP and collagen was induced by procedure. Whereas activated GpIIb-IIIa and P-selectin expression decreased 24 h and 48 h after procedure, PPA and PMP remained as elevated as before. Thus, flow cytometry is a reliable method for detection of fully activated platelets in whole blood samples. Annexin V binding analysis demonstrates the persistance of in vivo platelet activation, despite the use of antiaggregating agents.
Keywords: Human blood platelets; flow cytometry; annexin V; microvesiculation; unstable angina